Navigating Dual Expectations: A Qualitative Study of the Psychological Dynamics of the Youngest Child in Javanese Families - Nadha Khoirina; Lely Nur Azizah; Ya'lu Wala Yu’laa; Syifakh Herianto; Femita Adelina (International Conference on Psychology and Education (ICPE), 2024)
The position of the youngest child (ragil) in Javanese families provides a unique lens through which to examine the effects of birth order on psychological development within a traditional cultural context. Javanese culture presents a dual dynamic for the youngest child, who often receives heightened attention from family members while simultaneously facing significant expectations to care for aging parents in adulthood. This study explores the psychological dynamics and character development of the youngest child (ragil) in Javanese families, focusing on how family structure, parenting styles, and socio-economic conditions shape their development. Utilizing a qualitative approach, this research involves in-depth interviews with three youngest children aged 19-21 years, living with their parents and siblings. The findings reveal that the youngest child often receives special attention and support from parents, which contrasts with the experiences of older siblings. This preferential treatment, while beneficial in nurturing the youngest child, also comes with high expectations to fulfil familial responsibilities, especially as the family faces economic challenges. The study highlights how these children are encouraged to develop independence and resilience, balancing between the privileges and responsibilities they inherit. The impact of changing economic conditions and the burden of surpassing older siblings' achievements contribute to their character formation. The study's insights are contextualized within Javanese cultural norms and underscore the complex interplay between parental care, sibling dynamics, and individual development. The findings provide a deeper understanding of how cultural and familial factors influence the psychological growth of the youngest child, offering implications for parenting practices and family dynamics in similar cultural settings.